A new Bible translation : "the syntactic translation"? - Lubbe, John (Old Testament essays, 2009)
Over the past decades various versions of the Biblical text have appeared. Many appeared in response to the need to update the language of an older, yet popular version, such as the King James and the old Afrikaans translation. Thereafter versions appeared in which the translation per se was not altered, but notes were added of an encyclopaedic or homiletical sort. These were frequently labelled "study Bibles." The variety of translations and the inserted notes have in some sense assisted the average user of the Bible, whether preacher, teacher or reader, but have also further complicated the situation of understanding the text, since the new translations differ in their rendering and in the quality of the additional notes. In the light of these developments and the fact that standards of proficiency in the reading of Hebrew are often less than satisfactory among current church leaders, has the time not come for Biblical scholarship to provide clearer guidance in the syntactic structure of Hebrew prose and poetry in order to enhance the understanding of the text? Would a translation that reflects the Hebrew not fill a very glaring gap in the research tools that are available to students of the text?